Workplace violence against healthcare workers in rural health facilities of Bangladesh and their quality of life: A cross-sectional study - Haque, Md Atiqul; Ratan, Zubair Ahmed; Khan, Abid Hasan; Mousum, Sabrina; Towhid, Muhammad Ibrahim Ibne; Ullah, Md Enayet; Khan, Md Maruf Haque; Islam, Mohammad Tanvir (Bangabandhu Sheikh Mujib Medical University Journal, 2024)
Background: The prevalence of verbal and physical violence against healthcare workers (HCWs) is reportedly high in Bangladesh. We aimed to determine the prevalence and risk factors associated with violence against HCWs in Bangladesh. Methods: This cross-sectional study was done in May-June 2021 among 378 physicians and nurses working in 19 randomly selected rural government health facilities. A self-administered validated Bangla version of the WHOQOL-BREF questionnaire on workplace violence (WPV) and the quality of life (QoL) was used. Multiple logistic regression analyses were done to find out the independent risk factors of WPV. Results: The prevalence of overall WPV was about 48.0% (psychological 46.6%, physical 5.0%, and sexual harassment 1.9%). However, the WPV reporting rate was very low (27.8%). Being a male (aOR= 2.18; 95% confidence interval: 1.22−3.90) and a physician (aOR = 2.93; 95% CI: 1.56−5.52) had increased the likelihood of experiencing WPV. HCWs who were encouraged to report WPV were less likely to experience WPV (aOR = 0.36; 95% CI: 0.18−0.70). Study participants exposed to WPV had sig-nificantly lower QoL (P<0.01) in all the domains of WHOQOL-BREF (physical, psychological, social, and environmental). Conclusion: The study findings revealed that half of the HCWs working at rural government health facilities experienced WPV, which warrants proper investigation to adopt effective measures to reduce future occurrence. Moreover, the QoL of HCWs working in the aforementioned health facilities was significantly influenced by exposure to WPV.